From brand congruence to the ‘virtuous circle’: branding and the commercialization of public service broadcasting - Johnson, Catherine (Sage, 2013)
In debates about the commercialization of public service broadcasting little attention has been paid to the ways in which the public might experience the commercial and public service activities of public service broadcasters and the impact that this may have on attitudes towards public service broadcasting. This is despite the fact that public service broadcasters increasingly depend on public support for their continued survival. Using the case study of the BBC, this article examines the ways in which the corporation has adopted strategic brand management to negotiate the relationship between its commercial and public service activities. Focusing on specific examples of the BBC’s commercial and public services, the article reveals a tension between the corporation’s attempts to ensure that all activities support its public purposes and its need to ensure separation between public and commercial work. Focusing on the consumer’s experience of the BBC brand, the article argues that rather than seeing commercial activity and public service broadcasting as inherently contradictory, we should be looking at the ways in which public service broadcasters can better communicate the relationship between their commercial and public service activities while continuing to argue for the social and cultural value of publicly funded broadcasting.